1995
DOI: 10.1111/j.1432-1033.1995.0823d.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Characterization of Trimeric Cyanobacterial Photosystem I Complex with the Help of Recombinant Antibody Fragments

Abstract: A monoclonal antibody was derived from mice immunized with the native trimeric, photosystem I (PSI) complex from the cyanobacterium Synechococcus PCC 7002 which reacts with a conformational epitope of the PSI complex. As seen by immunoelectron microscopy, the mAb bound to the stromal side of the thylakoid membranes. The DNA sequence encoding variable regions of the mAb was cloned into recombinant plasmids, sequenced and expressed in Escherichia coli. ELISA, Western blots and immunoelectron microscopy provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The PSI complex in cyanobacteria is organized in the thylakoid membrane preferentially as trimers (Tsiotis et al, 1995;Karapetyan et al, 1999). We found that PSI trimers account for 70% and approximately 60% of total cellular chlorophyll in LL and HL, respectively (Table II).…”
Section: Discussionmentioning
confidence: 78%
“…The PSI complex in cyanobacteria is organized in the thylakoid membrane preferentially as trimers (Tsiotis et al, 1995;Karapetyan et al, 1999). We found that PSI trimers account for 70% and approximately 60% of total cellular chlorophyll in LL and HL, respectively (Table II).…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, unlike the nonoxygenic, monomeric bacterial reaction centers, photosynthetic reaction centers in oxygenic organisms are found as monomers (plant PSI), dimers (all PSII), or trimers (cyanobacterial PSI). Cyanobacterial PSI trimers have been reported in many published works (Boekema et al, 1987(Boekema et al, , 2001Almog et al, 1991;Kruip et al, 1993Kruip et al, , 1994Kruip et al, , 1997Tsiotis et al, 1995;Garczarek et al, 1998;Tucker and Sherman, 2000;Mangels et al, 2002;Bibby et al, 2003;Brecht et al, 2012), and the only existing crystal structure of a cyanobacterial PSI, from Thermosynechococcus elongatus BP-1 (Jordan et al, 2001), suggests that cyanobacteria PSI preferentially forms a trimer. Although there have been reports of trimeric forms of PSI in plants (Heinemeyer et al, 2004;Kouril et al, 2005), it is now widely accepted that plant PSI forms only monomeric complexes (Kitmitto et al, 1998;Kouril et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[21], but not for unicellular cyanobacteria Synecho coccus (now Thermosynechococcus) elongatus and Synechocystis PCC6803 [ 22 25]. The existence of the PSI trimers in the membranes of the unicellular cyanobacte ria was found using antibody [26] and electron microscopy [27]. The PSI trimer/monomer ratio in cyanobacterial membranes can be reversibly regulated: mainly trimeric complexes are isolated from membranes incubated with low salt, while preferably monomer com plexes are isolated from membranes after incubation under high salt conditions [28,29].…”
Section: Structure Of Psi Complex Of Cyanobacteriamentioning
confidence: 99%